Effect of a Deep Cryogenic Treatment on Wear and Microstructure of a 6101 Aluminum Alloy - Volker Franco Steier; Edgar Sobral Ashiuchi; Lutz Reißig; José Alexander Araújo (Advances in Materials Science and Engineering)
The aim of this work is to evaluate the effect of a deep cryogenic treatment (DCT) on the wear behavior and on the microstructure of an aluminum alloy. In order to compare the level of improvement on the wear resistance provided by the DCT with a more traditional technique, a test matrix which included DCT, CrN coated specimens, and combinations of both modification methods was conducted. The wear behavior was investigated using microabrasive wear tests. The cryogenic treated specimens proved to have similar low wear rates as the specimens coated with CrN. The most distinct improvement was reached with a combination of both techniques. In the case of the DCT, the performed microstructural analysis identified the generation of additional GP-zones as the reason for the improved wear resistance.